2012
DOI: 10.1016/j.jvs.2011.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patient outcomes between multiple ipsilateral iliac artery stents and isolated iliac artery stents

Abstract: Outcomes are similar for patients with CIA or EIA stents and for those with combined ipsilateral CIA and EIA stents. Late open conversions for iliac artery stent failure are uncommon and not influenced by the location or extent of prior iliac artery stent placement. Endovascular therapy for aortoiliac disease should be extended to consider selected patients with ipsilateral CIA and EIA stenoses/occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…[28][29][30] Other factors that have been reported to have significant impact on the patency rates from previous studies are ipsilateral superficial femoral artery occlusion, poor runoff, CLI, female gender, diabetes, and renal insufficiency. 7,9,31,32 None of these factors was significant in our cohort in the univariate or multivariate analysis for 1-or 5-year TLR.…”
Section: Discussionmentioning
confidence: 76%
“…[28][29][30] Other factors that have been reported to have significant impact on the patency rates from previous studies are ipsilateral superficial femoral artery occlusion, poor runoff, CLI, female gender, diabetes, and renal insufficiency. 7,9,31,32 None of these factors was significant in our cohort in the univariate or multivariate analysis for 1-or 5-year TLR.…”
Section: Discussionmentioning
confidence: 76%
“…The duration of hospital stay was associated with increasing patient age for elective and non‐elective admissions, but not with centre volume or patient sex. Previous studies have been too small to detect associations between procedural outcomes and these factors.…”
Section: Discussionmentioning
confidence: 98%
“…For elective procedures, there was also an association between female sex and postprocedure complications, which was confirmed by multivariable analysis, although the association (odds ratio 1·28, 1·09 to 1·49) was much less strong than for mortality. Reyes and co‐workers, in a study of 249 patients, found that female sex was an independent predictor of poor prognosis for primary patency after angioplasty, but most previous studies have been too small to detect the effect of sex on procedure‐related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the iliac segment subjected to endovascular treatment (common iliac artery and external iliac artery vs. common iliac artery) did not influence the limb salvage, reintervention, or primary patency rates. Similarly, Danczyk et al 13 compared the outcomes between multiple ipsilateral iliac artery stents and isolated iliac artery stents. They found that survival, reintervention-free survival, late open conversion-free survival, and amputation-free survival were similar between the patient groups (all p > 0.05).…”
Section: Discussionmentioning
confidence: 99%